Equações para predição de adiposidade corporal de portadores de doença renal crônica hemodialíticos - GUIMARÃES, Alana Caroline Amorim de Miranda (2019)
Introduction: Even though the effects of obesity in patients with chronic renal disease undergoing hemodialysis are not well enlightened yet, it’s known that central adiposity is associated with cardiovascular complications which are the main cause of morbidity and mortality in this population. Objectives: To determine equations from anthropometric measures and indicators in order to predict the percentage of total body fat (%BF) and android fat (AF) of chronic renal patients undergoing hemodialysis. Methods: Cross-sectional study which evaluated 323 renal patients undergoing hemodialysis from São Luís - MA. Has been measured: dry body weight; stature; waist (WC), neck (NC) and hip (HC) circumferences; sagittal abdominal diameter (SAD); and triceps (TSF), biceps (BSF), subscapular (SSF) and suprailiac (SISF) skinfolds. And has been calculated body mass index (BMI), waist-hip ratio, waist-to-height ratio (WHtR) and conicity index. The %BF and AF, in kg, were evaluated by means of double‐energy X‐ray absorptiometry (DXA). Correlations between the studied variables were analyzed by the Spearman coefficient. For the development of the equations the multiple linear regression analysis has been done, with subsequent cross-validation. Results: The individuals from the total sample presented average weight of 59,81 ± 11,43kg, average BMI of 23,43 ± 3,66kg/m2, %BF of 29,27 ± 9,33% and AF of 1,56 ± 0,92kg. The proposed model to predict the %BF was: %BF= 5,6 – 0,21weight – 0,20heigh + 0,29WC + 0,39HC + 0,16DCSI +0,46DCT – 2,68sex (R2=77,1%). The model chosen to estimate the AF in kg was: AF(kg)= -2,2 + 0,007weight – 0,015height + 0,045WC + 0,012HC + 0,013ΣSF + 0,044sex (R2=79,5%). Conclusion: The proposed equations to evaluate total and central body adiposity are capable of predict effectively the %BF and AF (kg) of chronic renal patients undergoing hemodialysis. Thus, when more accurate devices are not available, it is possible to use this tool that requires simple anthropometric measurements and that are usually measured in nutritional assessments.